Urban Sufism, Media and Religious Change in Indonesia - Luthfi Makhasin (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2016)
In this paper, I contend that Sufism is only preoccupied with initiating new disciples and performing emotive religious rituals. By focusing on Naqshbandi-Haqqani, I argue that Sufi group actively involves in propagating its teaching to the general public. I also argue that Sufi movement actively involves in public campaign, along with other Muslim groups with similar religious outlook, to respond the perceived growing influence of Salafism and political Islamism among Indonesian Muslims. It represents contemporary public face of Sufism and Sufi activism in Indonesia. At the heart of the argument of this chapter is to examine collective efforts to maintain Sunni orthodoxy (Ahlus Sunnah wal Jamaah) as a dominant religious norm, reclaim Sufism as a legitimate voice within Sunni orthodoxy and general Muslim community, oppose to Salafism and political Islamism, and rationalise Sufism to academic community in Indonesia. This chapter will demonstrate that active propagation through the internet plays a significant role in generating new Islamic consciousness with greater appreciation toward Sufi tradition among Indonesian Muslims. Sufism contributes not only to shape public religious discourse/morality, influence consuming patterns of urban upper-middle class Muslims, but also maintain moderate and peaceful Islam in Indonesia.